Design of adaptive backstepping congestion controller for TCP networks with UDP flows based on minimax. (December 2019) - Li, Zanhua; Liu, Yang; Jing, Yuanwei
Abstract: The congestion control problem of TCP network systems with user datagram protocol (UDP) flows is investigated in this paper. A nonlinear TCP network model with strict-feedback structure is first established. The unknown UDP flow is regarded as the external disturbance, and the maximum UDP flow is calculated by using the minimax approach. And then, a congestion control algorithm is proposed by using the adaptive backstepping approach. Meanwhile, the adaptive law is employed to estimate the unknown link capacity. The design of the adaptive law is to introduce a parameter mapping mechanism to limit the parameter identification range to a specified interval, thereby improving the estimation efficiency of the parameters. Furthermore, a state-feedback congestion controller is presented to make sure that the output of the system tracks the desired queue. The simulation results show the superiority and feasibility of the proposed method. Highlights: The UDP flow is addressed by the minimax method instead of H ∞ control. A novel congestion algorithm is presented to solve an adaptive tracking problem. The steady-state error of the closed-loop system satisfies the design requirements.